Recasts, prompts and noticing: A comparative study - Choo Siow Chin; Stefanie Pillai; Siti Zaidah Zainuddin (Universitas Syiah Kuala, 2021)
Noticing has been regarded as an important theoretical construct in the mechanism of how corrective feedback (CF) facilitates second language acquisition. However, to date, only a paucity of CF research has examined noticing triggered by different types of CF (i.e., recasts vs. prompts). The study is intended to fill in the gap by examining the relationships between type of CF and level of noticing. To that end, 105 Malaysian ESL learners were asked to perform four communicative tasks during which recasts and prompts were provided contingent upon the encounter of past tense errors.  To assess noticing, the study has employed a triangulated method using multiple elicitation procedures including diary writing, stimulated recall, and exit questionnaire. The results of the study revealed that both recasts and prompts were able to induce noticing the corrective intent, noticing the target of CF or form, noticing the gap, and noticing the rule. However, contrary to what was expected, recasts were able to promote higher levels of noticing across all noticing categories. Moreover, the greatest difference between recasts and prompts was found in noticing the gap. The study suggests that CF that provides exemplars of the target linguistic feature may promote higher levels of noticing the gap which may, in turn, increase the effectiveness of CF in L2 acquisition.